1096 Cardiac masses in children- a rare case of primary Cardiac Stage III Burkitt Lymphoma. (17th August 2022) - Ene, Elisabeta; Johns, Melonie; Jones, Caroline; Duong, Phuoc
Abstract : Aims: The unexpected diagnosis of bilateral large atrial masses in a child presenting to a DGH, later confirmed to have a very rare etiology, prompted literature review of cardiac tumours in paediatrics, their complications and prognosis. Methods: A 9-year-old girl presented to local hospital with 7-week history of migraine, and in the last week, reduced exercise tolerance, dyspnoea and abdominal swelling. On examination there was abdominal distension with shifting dullness, hepatomegaly, soft systolic murmur at LLSE. Abdominal USS confirmed ascites and dilated IVC. ECHO demonstrated 3 heterogenous mobile masses, 2 in the left atrium and 1 in the right atrium, with bilateral inflow obstruction and circumferential pericardial effusion ( figure 1 ). In the tertiary centre, she underwent surgical resection. The masses were irregular and encased in a gelatinous capsule which was friable ( figure 2 ). Histology confirmed Burkitt Lymphoma. Chemotherapy was commenced. On day 20 after surgery, a left atrial thrombus was identified and anticoagulation was started. 7 days later, the patient developed right hemiparesis and the thrombus was no longer present in the left atrium. MRI head confirmed left MCA infarct. The patient is undergoing neurological rehabilitation, with good progress. Results: Literature review: Cardiac tumours within the paediatric population are rare. The majority are benign- rhabdomyoma being the most prevalent in early life. Malignant cardiac tumours are reported to make up less than 10% of total paediatric cardiac tumours. Primary malignant cardiac tumours are 95% sarcoma, 5% lymphoma. 1 Primary lymphoma of the heart is very rare and usually located on the right side. A review in 2016 showed only 22 published cases of cardiac Burkitt Lymphoma of which 40% were associated with acquired immunodeficiency( HIV/AIDS or post transplant immunosupression). 2 In this case series, 50% of patients died within 6 weeks of diagnosis, however, a significant proportion of these patients received no treatment. Other publications suggest complete remission has been achieved in up to 60% of cases with aggressive early chemotherapy. 3 All forms of cancer can increase both the thromboembolic and bleeding risk due to alteration of several different coagulation pathways. Cardiac tumours have an added risk of thromboembolism, which is more significant in friable masses. 4 Conclusion: Learning Points: The presence of a cardiac tumour in the right atrium increases the probability of it being malignant. Burkitt lymphoma is a highly aggressive tumour, with rapid doubling time and quick progression of symptoms. 2 Although cardiac tumours are rare in children, the tumour itself or secondary thrombus formation can cause significant morbidity from cerebral embolization, especially when located in the left heart chambers. Despite complete tumour removal, thrombus formation remains a risk factor. (1)- Cardiac tumours in children. Uzun et al. Orphanet Journal of Rare Diseases 2007 (2) Burkitt Lymphoma presenting as intracardiac mass: Case report and review of literature. Chan et al. Am J of Case Reports 2016 (3) Long-term disease-free survival of patients with primary cardiac lymphoma treated with systemic chemotherapy and radiotherapy. Shin et al. Korean J Haematol. 2010 (4)-Cardiac masses and tumours. Basso et al. Heart. 2016